The Role Of International Law In Reducing Ship Piracy In The Waters Of The Horn Of Africa - Melvern N Sitorus; Seniwati Seniwati (Desentralisasi : Jurnal Hukum, Kebijakan Publik, dan Pemerintahan, 2024)
The Horn of Africa waters are the busiest trade routes and are often passed by thousands of merchant ships worldwide. Merchant ships must overcome the threat of Piracy in the Horn of Africa waters, and the danger comes from Somalia, the center of pirate operations. This article discusses how international law, more precisely the United Nations Convention on the Law of the Sea (UNCLOS), reduces acts of ship piracy in the Horn of Africa waters, either in the form of court sentences or by sending patrol teams and forming military operations under the auspices of the U.N. or operating under UNCLOS law to combat Piracy. Piracy or ship hijacking is a universal problem that the international community must consider because the impacts it causes, of course, have a global impact and disrupt the stability of the world economy of international trade, that is why must be eliminated from their roots, namely the failed Somali government. The novelty in this study is the need for more literature discussing the role of international law in reducing acts of ship piracy in the Horn of Africa waters.